Bank performance in achieving Islamic bank stability conditions: Evidence from Islamic Banks in Indonesia - Siyamto, Yudi (Kompartemen : Jurnal Ilmiah Akuntansi, 2023)
This study aims to analyze the effect of Islamic bank performance on Islamic bank stability in Indonesia. Research using monthly time series data from OJK Sharia Banking Statistics 2015-2022. The analytical tool uses ECM and ECT tests to test the long-term impact and short-term response of operational efficiency, liquidity and bank size on the stability of Islamic banks. The research results found that the performance of Islamic banks in terms of operational efficiency has a negative effect on the stability of Islamic banks in both the short and long term. Furthermore, liquidity has no effect on the stability of Islamic banks in the long term, but has a positive effect in the short term. While bank size has a positive effect on the stability of Islamic banks in the long term, it has no effect in the short term